COMPARISON OF PAIN SCALES USED IN ADULT NON-VERBAL CRITICAL CARE PATIENTS: A SYSTEMATIC LITERATURE REVIEW - Pınar Kaya; Yeşim Yaman Aktaş; Sevilay Erden (Yoğun Bakım Hemşireliği Dergisi)
ABSTRACTPurposeThe purpose of this study was to verify the literature evaluating the Behavioral Pain Scale, the Critical Care Pain Observation Tool, and the Nonverbal Pain Scale, which are routinely used to assess pain in the patient.MethodsThis study was a methodological systematic review. Herein, MEDLINE, OVID, Google Scholar, Science Direct, Scopus and PubMed databases were used from 2010 to 2024 (April). The mnemonic PICOS was used to define the eligibility criteria in this study. Data were extracted, summarized, evaluated using published compatibility and usability classifications.FindingsResearch has verified that the Behavioral Pain Scale, the Critical Care Pain Observation Tool, and the Nonverbal Pain Scale are legitimate and reliable scales for assessing pain in patients who cannot communicate verbally. Pain assessment tools were similar in terms of compatibility and usability, with the exception of two studies.ConclusionsOf all the pain assessment units considered, Behavioral Pain Scale and the Critical Care Pain Observation Tool were found to be most appropriate for critical care patients at hemodynamic risk. The systematic and consistent use of an appropriate pain assessment tool in the critical care setting optimizes and improves pain control.